CONFIGURATIONS OF A TRANSPARENT BUSINESS DEVELOPMENT ENVIRONMENT AS A CONDITION FOR ACHIEVING STRATEGIC CHANGES - SHKURENKO, Olga; PROTSENKO, Valentina; PODOLIAKIN, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article proves the necessity of ensuring the transparency of the environment in promoting strategic changes. Transparency is a key condition for the effective development of enterprises on an innovative trajectory, because the latest management technologies require the availability of transparency and openness of information for making management decisions. It is reliable and complete information about the current state of the enterprise that allows you to establish relations with partners and outline directions for further development. Attention is focused on the fact that information about the activities of enterprises should be accessible, open and transparent. The legal, economic and social aspects of understanding the category "transparency" are highlighted. The role of transparency in promoting strategic changes has been proven due to the availability of information, openness in making management decisions, involvement of stakeholders, monitoring of development, open exchange of information, interaction with the public. The principles of compliance with the transparency of the enterprise development environment are highlighted, namely openness, completeness, timeliness, integrity of information and influence on the decisions made. When ensuring the transparency of the environment, one should take into account the peculiarities of each of its components, which form stable relationships with investors and other interested parties and cover various aspects of the enterprise's activity, namely socially responsible, financial, technological, legal, managerial. A scheme for ensuring the transparency of the enterprise development environment is proposed as a condition for achieving strategic changes. Transparency creates a favorable environment for adapting to changes in the business environment, openness in relations allows us to respond more quickly to challenges and changes in the market.
Keywords: environmental transparency; enterprise development; strategic changes; transparency; software